If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(2x + -5) = 16 + 2x Reorder the terms: -6(-5 + 2x) = 16 + 2x (-5 * -6 + 2x * -6) = 16 + 2x (30 + -12x) = 16 + 2x Solving 30 + -12x = 16 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 30 + -12x + -2x = 16 + 2x + -2x Combine like terms: -12x + -2x = -14x 30 + -14x = 16 + 2x + -2x Combine like terms: 2x + -2x = 0 30 + -14x = 16 + 0 30 + -14x = 16 Add '-30' to each side of the equation. 30 + -30 + -14x = 16 + -30 Combine like terms: 30 + -30 = 0 0 + -14x = 16 + -30 -14x = 16 + -30 Combine like terms: 16 + -30 = -14 -14x = -14 Divide each side by '-14'. x = 1 Simplifying x = 1
| 4-(-6)/x2-4 | | 3(2x-3)=-24 | | 24+3x=3 | | 9-x+3x-2-9x=0 | | X/2-8=-14 | | 6log^8x+2=0 | | 6log^8+2=0 | | -22=g+15 | | 4/x=[72/40]2 | | h/5-h/3=7/15 | | 8(5-2v)-8=3v+13 | | -1/3x-1/2=3/5 | | -5+12=16x-2-15x | | 2(4x)=2x | | 4(3x+1)=3x-7x | | 7.7a-5.8a= | | 13y=12(y+8) | | X-(x*0.05)=800 | | 16y=40+8y | | -9(x-9)=7x+17 | | 1+44=-5(8x-9) | | -22=4(v-8)-6v | | 123-v=179 | | s^2=45-4s-s^2 | | .3/.2=18/? | | X/3- | | 6w+3w=27 | | 3x-450=2816 | | V/-3.3=-14.8 | | -5(5n-5)+3n=0 | | -3y-8x=12 | | 8sin(2pi/3) |